Feline sporotrichosis: Clinical conduct, diagnosis and treatment recommended in the municipality of Vitória- ES (Research, Society and Development, 2022)
Sporotrichosis is a zoonosis transmitted by Sporothrix sp that causes cutaneous and disseminated lesions, with frequent cosmopolitan distribution in regions with hot and humid climates. We analyzed 270 cases, 95 of which presented clinical signs suggestive of sporotrichosis, being analyzed and verified. To collect the material, physical or chemical contention (0.2ml/kg of Tiletamine 125mg + Zolazepan 125mg) was performed. The material was collected by swabs, or by imprint method, in extensive and exudative lesions, and identified, packaged and sent to the laboratory for confirmation of the disease. 95 animals were diagnosed with sporotrichosis; 23 (24.0%) were euthanized immediately because they arrived at the clinic with advanced stages of the disease and 72 (76.0%) were submitted to the proposed treatment (itraconazole or itraconazole + potassium iodide). After treatment, 69 (94.2%) were clinically cured and 3 (5.8%) were euthanized due to therapeutic inefficiency.  The highest incidence of this pathology was observed in animals from regions surrounded by mangroves, adjacent forests, with low-income populations and lack of sanitary services.Therefore, it is concluded that felines between 23 months to 35 weeks, classified in stages I and II of treatment, obtained satisfactory cure rates and the therapeutic protocol used by the sporotrichosis service of the zoonosis, ,  department of Zoonosis, of the Environmental Health Surveillance Center. it was effective.